Teachers Perceptions of Google Classroom: Revealing Urgency for Teacher Professional Learning - Martin, Brandy A. (Canadian Journal of Learning and Technology, 2021)
As the use of educational technology is at the forefront of today’s educational revolution, it is imperative that educators are employing online learning environments such as Google Classroom to enhance 21st century pedagogy and student learning. Through this mixed method research study, it has been concluded that using Google Classroom will assist educators in creating learning environments which boast organization, accessibility, mobility, and 21st century learning skills. This research reveals there continues to be gaps between the possibilities of eLearning and the training of teachers to use it and develop their teaching practices within a technological mainstream that moves beyond positivism about its value. The researcher recommends that teachers receive immediate and sustained professional learning regarding the use of Google Classroom. This learning should focus on the pedagogical side of technology integration in order to enhance 21st century learning.